Faktor-faktor yang Memotivasi Pemilihan Karir Mahasiswa - Dhina Sri Widyaningsih; Theresia Mentari; Verra Rizki Amelia (Balance: Media Informasi Akuntansi dan Keuangan, 2023)
This research aims to identify factors that motivate career choices for accounting students. This motivation is measured by wage variables, professional training, professional recognition, social values, work environment, labour market considerations and personality. Data collection is carried out through the dissemination of questionnaires to students of the University of Palangka Raya accounting. A sample of 30 respondents. The data was analyzed using SPSS version 23. The results of the analysis show that the factors that motivate accounting students in choosing careers are the variables of professional recognition, social values and personality.